1995
DOI: 10.1111/j.1365-246x.1995.tb01852.x
|View full text |Cite
|
Sign up to set email alerts
|

α/β phase transition in quartz monitored using acoustic emissions

Abstract: SUMMARY It is usually suggested that thermal cracking in a quartz‐bearing rock results from the anomalously high volumetric expansion coefficients of quartz (e.g. Simmons & Cooper 1978). It has also been recognized that thermal expansion mismatch and mineral anisotropy contribute to thermal cracking in materials that consist of a polycrystalline aggregate composed of several anisotropic minerals even in the absence of a temperature gradient (Friedrich & Wong 1986). Experiments investigating thermal cracking in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
1
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 273 publications
(100 citation statements)
references
References 14 publications
4
92
1
3
Order By: Relevance
“…We can conclude that (1) mineralogical changes (and in particular decarbonation) and phase transitions give raise to the most significant changes in the elastic moduli of rocks: e.g., decarbonation (in the case of carbonates, this study), the α-β quartz transition (in granites and sandstones, see Glover et al, 1995), and the loss of water from zeolites (in pyroclastic deposits, see Heap et al, 2012). In the absence of chemical alteration, and when the rocks already contain an extensive thermal microcrack network [the case for the basalt of Heap et al (2009) and the andesite of Petrakova et al, 2012], no changes were observed.…”
Section: Accepted M Manuscriptmentioning
confidence: 69%
“…We can conclude that (1) mineralogical changes (and in particular decarbonation) and phase transitions give raise to the most significant changes in the elastic moduli of rocks: e.g., decarbonation (in the case of carbonates, this study), the α-β quartz transition (in granites and sandstones, see Glover et al, 1995), and the loss of water from zeolites (in pyroclastic deposits, see Heap et al, 2012). In the absence of chemical alteration, and when the rocks already contain an extensive thermal microcrack network [the case for the basalt of Heap et al (2009) and the andesite of Petrakova et al, 2012], no changes were observed.…”
Section: Accepted M Manuscriptmentioning
confidence: 69%
“…should not be expected between 100 and 200 °C, but become more significant above 400 or 500 °C (Tian et al 2012). Indeed, thermal cracking experiments have shown that the greatest changes are likely to be achieved once the temperature has exceeded 573 °C, i.e., the α/β transition of quartz (Glover et al 1995). Li et al (2011) investigated the change in the longitudinal wave velocity and mechanical behavior of sandstone after different high-temperature treatments using triaxial unloading experiments.…”
Section: Discussionmentioning
confidence: 97%
“…Many experimental investigations have demonstrated that high temperature significantly affects the physical properties of sandstones (Heuze 1983;Glover et al 1995;Chopra 1997;Zhang et al 2001;Tang et al 2011;Zhao et al 2012). Analytical and numerical modeling of thermomechanical processes in sandstones have shown that variations in rock physical properties (such as bulk density, porosity, compressional wave velocity, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Temperature equilibrium in the sample was reached after approximately 75 minutes, and the thermal gradient along the sample was less than 1°C/cm. Experiments were performed at temperatures from 20°to 75°C because previous studies suggest (1) that thermal cracking in many crustal rocks commences around 100°C [Glover et al, 1995], so is likely to be minimised or precluded over this range, and (2) that this range is sufficient to significantly influence the rate of stress corrosion [Meredith and Atkinson, 1983].…”
Section: Experimental Materials and Methodologymentioning
confidence: 99%